A 1-dimensional dynamic model for a sorption-compressor cell. (April 2017) - Wu, Y.; Mulder, T.; Vermeer, C.H.; Holland, H.J.; ter Brake, H.J.M.
Highlights: A 1-D dynamic model is developed for designing sorption-compressor cells. Simulation cases are discussed for understanding the dynamics in sorption cells. He and Ne experiments operating at 77 K were carried out to validate the model. Abstract: Sorption-based cooler is considered as an excellent candidate for the vibration-free cooling at cryogenic temperature. In a such cooler, the sorption compressor is the most critical module. To design a sorption-compressor, effective numerical models are essential which allow one to simulate the details of the heat and mass transfer within the sorption-compressor cell, predict the system performance and optimize various parameters. This paper presents a 1-dimensional dynamic model for a sorption-compressor cell, which is based on extensive adsorption-isotherm measurements and realistic thermal properties of materials at low temperatures. This numerical model combines the mass and energy equations while the momentum equation is skipped. It assumes the pressure to be uniform within the cell. However, the convection term in the energy equation is evaluated in this model with proper approximation without calculating the velocity field. A typical simulation case is presented to understand the details during a sorption compression that occur in the sorption-compressor cell. Experiments based on helium and neon operating at 77 K (liquid nitrogen temperature) were carried out to validate this model. The measured compressor performance was deviated from the simulation about 18%, but that is a reasonable inaccuracy for design propose and is well reasoned. Such 1-D dynamic model is qualified to be further used to design sorption compressor.